2021
DOI: 10.1016/j.jhazmat.2020.124021
|View full text |Cite
|
Sign up to set email alerts
|

Bio-based and cost effective method for phenolic compounds removal using cross-linked enzyme aggregates

Abstract: Bio-based and cost effective method for phenolic compounds removal using cross-linked enzyme aggregates

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 52 publications
2
9
0
Order By: Relevance
“…Alteration of the enzyme tertiary structure by one of the components required for CLEA preparation or steric hindrance within the aggregate of high particle size hampering inner enzyme activity can also explain the decrease in activity. Hence, the choice of precipitant, cross-linker, and ratio of cross-linker protein is a critical step for maintaining required flexibility of the structure for high activity [185]. These parameters strongly depend on the enzyme, making the CLEA technology delicate [174].…”
Section: Cross-linked Enzyme Aggregates (Cleas)mentioning
confidence: 99%
“…Alteration of the enzyme tertiary structure by one of the components required for CLEA preparation or steric hindrance within the aggregate of high particle size hampering inner enzyme activity can also explain the decrease in activity. Hence, the choice of precipitant, cross-linker, and ratio of cross-linker protein is a critical step for maintaining required flexibility of the structure for high activity [185]. These parameters strongly depend on the enzyme, making the CLEA technology delicate [174].…”
Section: Cross-linked Enzyme Aggregates (Cleas)mentioning
confidence: 99%
“…These biological catalysts have immense industrial potential and have found application in multiple biotechnological fields such as, biosensors but also in bioremediation, for example the elimination of synthetic dyes from textile industry and the polymerization of phenolic compounds (Bilal et al, 2017a;Gholami-Borujeni et al, 2011;Sellami et al, 2021;Thenmozhi & Narayanan, 2017). Despite the effectiveness of peroxidases in hazardous compounds degradation, an application on an industrial scale cannot be envisaged in a free form, which is often associated with a lack of operational and storage stability.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Insolubilization gives more interesting mechanical and biochemical properties with an improvement of the efficiency and stability of the biocatalyst. In addition, the immobilized enzymes offer more advantages, including a reduction in the reaction time, help to minimize microbial contamination, and probably the most important features for large scale application, an easy separation of the biological catalyst from the reaction medium and the ability to operate continuously (Bilal et al, 2017a;Bilal et al, 2018a;Sellami et al, 2021). It is obvious that the application of peroxidases for environmental and biotechnological purposes is a topical research area.…”
Section: Introductionmentioning
confidence: 99%
“…The methods for protein cross‐linking mainly include physical, chemical and enzymatic cross‐linking, among which, enzymatic cross‐linking has been an important part for protein modification. At present, the most widely used enzymes that can catalyse protein cross‐linking are transglutaminase (TGase), lipoxygenase, polyphenol oxidase, peroxidase and so on (Liu et al ., 2021a; Sellami et al ., 2021). Among them, one of the commonly used enzymes is TGase (Adamiak & Sionkowska, 2020).…”
Section: Introductionmentioning
confidence: 99%